2017
DOI: 10.19173/irrodl.v18i3.2845
|View full text |Cite
|
Sign up to set email alerts
|

Approaches Reflected in Academic Writing MOOCs

Abstract: Since it was first introduced in 2008, Massive Open Online Courses (MOOCs) have been attracting a lot of interest. Since then, MOOCs have emerged as powerful platforms for teaching and learning academic writing. However, there has been no detailed investigation of academic writing MOOCs. As a result, much uncertainty still exists about the differences of writing MOOCs compared with traditional types of writing instruction in the classroom. Drawing on historical emphases in writing instruction, five approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Currently, a change in expectations has emerged around academic writing, and it has become increasingly evident that a much longer and gradual orientation in the process of research and information gathering is desirable to better meet the needs of contemporary students (Hamilton, 2018). On the basis of historical emphasis on writing instruction, five approaches are illustrated, namely, skills, creative writing, process, social practice, and socio-cultural perspective (Kwak, 2017). Academic writing is thus conceived as a way in which young people can construct their own according to elements that provide academic rigor through an efficient interaction with texts.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a change in expectations has emerged around academic writing, and it has become increasingly evident that a much longer and gradual orientation in the process of research and information gathering is desirable to better meet the needs of contemporary students (Hamilton, 2018). On the basis of historical emphasis on writing instruction, five approaches are illustrated, namely, skills, creative writing, process, social practice, and socio-cultural perspective (Kwak, 2017). Academic writing is thus conceived as a way in which young people can construct their own according to elements that provide academic rigor through an efficient interaction with texts.…”
Section: Introductionmentioning
confidence: 99%
“…Documents such as national policy documents, laws and regulations, industry norms, enterprise norms, national standards and international standards should adopt the latest official documents [9]. Documents should have practical reference value, relevant requirements of catalogue reference (digital library standards and specifications), version number, release date, publishing unit and use scope should be clear.…”
Section: K Teaching Resourcesmentioning
confidence: 99%
“…To observe the actual condition of the students, the researchers conducted a preliminary research. It was found that unfavorable conditions were experienced in many of academic writing classes (Kwak, 2017;Rakedzon & Baram-Tsabari, 2017). To name but a few, the lack of face-to-face time to accommodate the process of writing activities (Aliweh, 2011;Moloudi, 2011), lack of ability to utilize learning resources (Holmes et al, 2018), lack of media to facilitate students' writing exercises (Bilal et al, 2013), and less involvement of the cognitive process to improve the writing quality (Knox, 2017).…”
Section: Introductionmentioning
confidence: 99%